Cell encapsulation spatially alters crosslink density of poly(ethylene glycol) hydrogels formed from free-radical polymerizations. (June 2020) - Chu, Stanley; Maples, Mollie M.; Bryant, Stephanie J.
Abstract: Photopolymerizable poly(ethylene glycol) (PEG) hydrogels are a promising platform for chondrocyte encapsulation and cartilage tissue engineering. This study demonstrates that during the process of encapsulation, chondrocytes alter the formation of PEG hydrogels leading to a reduction in the bulk and local hydrogel crosslink density. Freshly isolated chondrocytes were shown to interact with hydrogel precursors, in part through thiol-mediated events between dithiol crosslinkers and cell surface free thiols, depleting crosslinker concentration and causing a reduction in the bulk hydrogel crosslink density. This effect was more pronounced with increasing cell density at the time of encapsulation. Encapsulation of chondrocytes in fluorescently labeled hydrogels exhibited a gradient in hydrogel density around the cell, which was abrogated by treatment of the cells with the antioxidant estradiol prior to encapsulation. This gradient led to spatial variations in the degradation behavior of a hydrolytically degradable PEG hydrogel, creating regions devoid of hydrogel surrounding cells. Collectively, findings from this study indicate that the antioxidant defense mechanisms in chondrocytes alter the resultant properties of PEG hydrogels formed by free-radical polymerizations. These interactions will have a significant impact on tissue engineering, affecting the local microenvironment around cells and how tissue grows within the hydrogels. Statement of Significance: Cell encapsulations in synthetic hydrogels formed by free-radical polymerizations offer numerous benefits for tissue engineering. Herein, we studied cartilage cells and identified that during encapsulation, cells interfered with hydrogel formation through two distinct mechanisms. Thiol-mediated events between monomers led to monomer depletion and a lower crosslinked hydrogel. Cells' antioxidant defense mechanisms interfered with free-radicals and inhibited hydrogel formation near the cell. These cell-mediated effects led to softer hydrogels and created unique hydrogel degradations patterns causing rapid degradation around the cells. The latter has benefits for tissue engineering, where these regions provide space for tissue growth. Overall, this study demonstrates that cells play a key role in how the hydrogel structure forms when cells are present. Graphical abstract: Image, graphical abstract